Answer: y = x + 1
Explanation:
The equation of a straight line can be represented in the slope-intercept form, y = mx + c
Where c = intercept
Slope, m =change in value of y on the vertical axis / change in value of x on the horizontal axis
change in the value of y = y2 - y1
Change in value of x = x2 -x1
y2 = final value of y
y 1 = initial value of y
x2 = final value of x
x1 = initial value of x
From the graph,
y2 = 6
y1 = 2
x2 = 5
x1 = 1
Slope,m = (6 - 2)/(5 - 1) = 4/4 = 1
To determine the intercept, we would substitute x = 1, y = 2 and m= 1 into y = mx + c. It becomes
2 = 1 × 1 + c
2 = 1 + c
c = 2 - 1
c = 1
The equation becomes
y = x + 1